تكريس حقوق الإنسان في الجـــزائر المجلس الوطني لحقوق الإنسان نموذجا - بادة، طارق; ماجدة، تجاني; تابعي، محمد (جامعة الوادي University of El Oued, 2024)
إن تكريس الحقوق والحريات في الدستور هو عماد الحكم العادل الذي تستمد منه أي سلطة شرعيتها، وهو مقياس للديموقراطية وتعزيز دولة القانون والمؤسسات، تلك المؤسسات التي حاولت الجزائر من خلال انشائها اكتساب مكانة مرموقة في منظومة حقوق الإنسان بالنظر إلى الأدوار التي تلعبها، لتصبح الفاعل وطنيا والشريك دوليا. إن إقرار المجلس الوطني لحقوق الإنسان يعتبر مواكبة للتطور المؤسساتي الدولي لتعزيز وحماية حقوق الإنسان والرقابة عليها، والذي أنشئ بموجب التعديل الدستوري لعام 2016 بنص المادتين 198 و 199 ، ثم صدور القانون رقم 13 - 16 بتاريخ 03 نوفمبر 2016 ، الذي ينظم المجلس الوطني لحقوق الإنسان ، والذي أدى لاعتباره هيئة دستورية يلاحظ أنها تتوافق مبدئيا مع المعايير الدولية لهيئة الأمم المتحدة. إن مضمون هذا القانون يُبين اختصاصات هذا المجلس وبنيته العضوية، تساهم استقلالية المجلس وطريقة تعيين أعضائه، في دعم وحماية وترقية حقوق الإنسان بالجزائر، بالإضافة لعمليات الرقابة على أي انتهاكات مستقبلية، كما يتمتع بعدة صلاحيات في مجال ترقية وحماية الحقوق والحريات، لاسيّما تلقي ودراسة الشكاوى وهو ما من شأنه تعزيز مكانته في النظام الدستوري الجزائري. Enshrining rights and freedoms in the constitution is the foundation of just governance from which any authority derives its legitimacy. It is a measure of democracy and the strengthening of the state of law and institutions. These institutions, through their establishment, Algeria tried to gain a prominent position in the human rights system in view of the roles they play, to become a national actor and a partner. Internationally. The approval of the National Council for Human Rights is considered keeping pace with the international institutional development to promote, protect and monitor human rights, which was established pursuant to the constitutional amendment of 2016 with the text of Articles 198 and 199, then the issuance of Law No. 13-16 dated November 3, 2016, which regulates the National Council for Human Rights, Which led to it being considered a constitutional body, and it is noted that it is in principle compatible with the international standards of the United Nations. The content of this law explains the powers of this Council and its membership structure. The Council’s independence and the method of appointing its members contribute to supporting, protecting and promoting human rights in Algeria, in addition to monitoring any future violations. It also has several powers in the field of promoting and protecting rights and freedoms, especially receiving and studying complaints. Which would strengthen his position in the Algerian constitutional system.
ماستر سياسة عامة